PENDEKATAN PSIKOLOGI AGAMA DALAM SEKTOR PERTANIAN UNTUK PENGEMBANGAN EKONOMI WILAYAH KECAMATAN SEMPARUK - Yuniarti, Desi; Rosalinda, Rosalinda; Ubabuddin, Ubabuddin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The agricultural sector is one of the key sectors in the economy of Sambas Regency, especially in Semparuk District. With abundant natural resources and a supportive climate, the agricultural potential in this area can be the main driver in improving people's welfare and accelerating economic development. This study aims to analyze the potential of the agricultural sector in Semparuk District and provide recommendations for appropriate development strategies. The research approach uses a qualitative descriptive method, with data collection through interviews, observations, and documentation. The results of the study indicate that the agricultural sector in Semparuk District has great potential in the development of food crops, horticulture, and plantations. However, there are several obstacles such as access to modern agricultural technology, inadequate infrastructure, and limited human resources. Therefore, supportive policies are needed, increasing farmer capacity, and optimizing land use to develop the agricultural sector in this area. The approach of religious psychology in the development of the agricultural sector in Semparuk District plays an important role in strengthening farmer motivation, strengthening social solidarity, and encouraging sustainable agricultural practices